Tumor necrosis factor suppresses interleukin 10 in peripheral B cells via upregulating Bcl2‐like protein 12 in patients with inflammatory bowel disease. (24th January 2017) - Guo, Xiutian; Li, Mao‐Gang; Li, Shan‐Shan; Liu, Feng‐Hua; Liu, Zhan‐Ju; Yang, Ping‐Chang
Abstract : The pathogenesis of the immune regulation dysfunction is unclear. Bcl2‐like protein 12 (Bcl2L12) has immune suppression function. This study tests a hypothesis that tumor necrosis factor (TNF) increases Bcl2L12 to suppress the expression of interleukin (IL) 10 in peripheral B cells of patients with inflammatory bowel disease (IBD). In this study, peripheral blood samples were collected from IBD patients and healthy controls. B cells were isolated from the blood samples. The expression of IL‐10 and Bcl2L12 in B cells was analyzed by quantitative reverse transcription polymerase chain reaction and Western blotting. We observed that the expression of Bcl2L12 in the peripheral B cells was higher in IBD patients than that in healthy controls. The IL‐10 levels in B cells were negatively correlated with the expression of Bcl2L12. Exposure of B cells to TNF in the culture enhanced the expression of Bcl2L12. The Bcl2L12 mediated the effects of TNF on suppression of IL‐10 in B cells. In conclusion, Bcl2L12 mediates the effects of TNF to suppress the expression of IL‐10 in B cells. The data suggest that Bcl2L12 may be a therapeutic target for the treatment of IBD.